PERANCANGAN MEDIA KAMPANYE PELESTARIAN KAWASAN KARST MAROS - PANGKEP SEBAGAI MEDIA EDUKASI PUBLIK - David Magetanapuang; Niken Savitri Anggraeni; Achmad Mucharam; Kristianus Haryandi; Win Rico (Commed Jurnal Komunikasi dan Media, 2023)
Karst is a rocky area that is known and categorized as an area with the title of natural beauty because of its unique shape, but it is rarely known to the wider community that karst areas hold a lot of potential and historical values, for example, the karst area in Maros- Pangkep that needs to be preserved. Preservation is considered difficult to realize because there are many mining permits for karst areas that exist for the manufacture of raw materials for cement and marble. Seeing the large number of people at large who do not understand what karst is and what its potentials are in it, the authors designed a social campaign for the preservation of karst areas using promotional media that can educate the public. This social campaign invites the general public to take part in safeguarding the karst area and use it more wisely. In designing this social campaign, theories such as layout theory, color theory, typography theory, and environmental theory are used. Main focus of the social campaign of this karst area is for the environmental preservation and human survival in the future.